Developing Interactive Media in Environmental Pollution Learning - Muhammad Yassir; Habibul Akram; Muhammad Tahir; Riyan Maulana; Husainah Yusuf (Yayasan Zia Salsabila, 2026)
This study aims to explore the development of interactive media for learning about environmental pollution and to test how suitable the media is as a learning tool. The methodology used in this study is research and development, which consists of four stages, namely: (1) identification of potential and problems, (2) data collection, (3) product design, and (4) design validation. The data collection technique used in this study is a questionnaire distributed to four validators, consisting of two supervising lecturers and two experts to assess the feasibility of the learning interactive media related to the theme of environmental pollution that has been developed. From the results of the study, it can be concluded that: (1) the design of the learning interactive media related to environmental pollution consists of devices such as an infocus, laptop, and Compact Disc. (2) The development of learning interactive media about environmental pollution, based on the results of the feasibility test and recommendations from expert validators on the questionnaire is declared suitable for use as a biology learning interactive media with very high criteria.